(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Childhood obesity has been recognized as a major public health concern. The purpose of this study was to determine specific shifting patterns of BMI and skinfold fatness across different age and sex groups between 1985/87 and 2012. Methods: The data of 9,366 children aged 8-15 years from two nationally representative surveys, i.e., 1985/87 National Children and Youth Fitness Study I & II and 2012 National Health and Nutrition Examination Survey National Youth Fitness Survey, were analyzed. Specifically, changes of BMI-based obesity prevalence and shifting patterns of BMI, height, weight, skinfold body fat percentage (skinfold-fat%), subscapular skinfold, and triceps skinfold from 1985/87 to 2012 were estimated by age and sex using the 1985/87 quartiles as the baseline. Results: Significantly increased obesity prevalence were reconfirmed for both boys (12.12%, P <.001) and girls (3.53%, P <.001) from 1985/87 to 2012. Except for height, all other measures in 2012 experienced an unbalanced shifting pattern, mainly from other quartiles into the 4th quartile of 1985/87. Conclusion: The shifting of both boys’ and girls’ BMI and skinfold-fat% were all concentrated in the 4th quartile of 1985/87, indicating not only that there was a significant increase in BMI and skinfold-fat% in the U.S. children from 1985/87 to 2012, but also into the overweight and obese subgroups, which serves as a serious warning for childhood obesity epidemic and public health.